MASA DEPAN KEBIJAKAN PUBLIK GLOBAL BERBASIS AMERIKA SERIKAT - Jonson Rajagukguk; L Primawati Degodona (Jurnal Ilmu Sosial Dan Politik, 2021)
As a nation that is scientifically and technologically strong, the United States, which is called the world police, is certainly not an exaggeration. Public policies made by the United States are always loaded with economic interests. Regional domination framed by equal state relations on the basis of human rights has always been the entry point for the American nation in carrying out domination politics. Public policy made by the United States is certainly oriented to its interests. Naturally, the concept of the American nation Number one by its leaders has certainly made its global policy always oriented to its interests. In the current global arena, the United States of America always makes policies that benefit itself in this case its economic interests.